2014
DOI: 10.1681/asn.2013060656
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Evokes Unique Segment-Specific Vasoconstriction of the Renal Microvasculature

Abstract: Sphingosine-1-phosphate (S1P), a bioactive sphingolipid metabolite, has been implicated in regulating vascular tone and participating in chronic and acute kidney injury. However, little is known about the role of S1P in the renal microcirculation. Here, we directly assessed the vasoresponsiveness of preglomerular and postglomerular microvascular segments to exogenous S1P using the in vitro blood-perfused juxtamedullary nephron preparation. Superfusion of S1P (0.001-10 mM) evoked concentration-dependent vasocon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
41
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 56 publications
(102 reference statements)
5
41
0
1
Order By: Relevance
“…In a previous study, authors demonstrated that the renal vascular bed was endowed with functional S1P 1-2 receptors 2 that mediated vasoconstriction which was attenuated by L-type calcium channel blockers. 2 Thus, the present contribution provides a confirmation of the role for voltage-gated calcium influx and further extends observations to show that intracellular calcium stores are less important for the response, that Rho-kinase is involved in signal transmission as in retinal arterioles 4 and that blockers of reactive oxygen species attenuated S1P responsiveness. Other studies suggest that this pathway may contribute to resting renal vascular tone as renal blood flow was increased in S1P 2 receptor knockouts and addition of S1P 2 receptor antagonists increased afferent arteriolar diameter at baseline conditions.…”
supporting
confidence: 78%
See 3 more Smart Citations
“…In a previous study, authors demonstrated that the renal vascular bed was endowed with functional S1P 1-2 receptors 2 that mediated vasoconstriction which was attenuated by L-type calcium channel blockers. 2 Thus, the present contribution provides a confirmation of the role for voltage-gated calcium influx and further extends observations to show that intracellular calcium stores are less important for the response, that Rho-kinase is involved in signal transmission as in retinal arterioles 4 and that blockers of reactive oxygen species attenuated S1P responsiveness. Other studies suggest that this pathway may contribute to resting renal vascular tone as renal blood flow was increased in S1P 2 receptor knockouts and addition of S1P 2 receptor antagonists increased afferent arteriolar diameter at baseline conditions.…”
supporting
confidence: 78%
“…1 New information on S1P signalling of potential therapeutic relevance is obtained, and the general concept is confirmed that renal pre-glomerular vascular reactivity relies significantly on calcium influx through voltage-gated calcium channels. The authors showed previously that S1P caused selective renal afferent but not efferent vasoconstriction, 2 and in conjunction with increased S1P release in pathophysiological situations like sepsis and ischaemia-reperfusion incidents, this effect could be relevant in acute kidney injury with parallel decreases in renal blood flow and GFR. Control of renal vascular resistance is physiologically important for the maintenance of stable renal blood flow and glomerular filtration rate.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Interestingly, selective deletion of endothelial S1P1 (Ham et al, 2014) or proximal tubule S1P1 (Bajwa et al, 2010) exacerbates renal ischemia/reperfusion injury, suggesting a cross-talk between the renal microvasculature and tubular epithelium during renal ischemia, which has also been suggested to occur during sepsis (Mayeux and Macmillan-Crow, 2012). Recent studies in the kidney also suggest that S1P could be a physiologic regulator of preglomerular vascular tone (Guan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%